Feasibility Analysis of ERP Implementation and Demand Forecasting at RM Pondok Ciung Tanjungpinang - Kelvin, Kelvin; Zai, Immanuel; Qadri, Rizni Aulia; Amanda, Nasyah; Melissa, Melissa; Saputra, Eric Gilbert; Wiliyan, Hendy (prodima@fe.uika-bogor.ac.id, 2023)
This study aims to analyze the feasibility of implementing ERP in Supply Chain Management with a qualitative approach and measuring demand forecasting quantitatively in UMKM RM Pondok Ciung Tanjungpinang. Data was obtained by the author through direct interviews. Data is managed using the Weighted Moving Average and Exponential Smoothing formulas which will then be tested for error rates. The findings of this study are that RM Pondok Ciung uses Majoo as a Point of Sales (POS) system and the method that is suitable for demand forecasting is the exponential smoothing method which is tested with Mean Square Error (MSE) and Mean Absolute Error (MSE).